Strengthening to seismic action of reinforced columns with rectangular cross-section - Marques, Pedro Gonçalo Faustino (2015)
The first part of this research work regards the assessment of the mathematical modelling of reinforced concrete columns confined with carbon fibre (CFRP) sheets under axial loading. The purpose was to evaluate existing analytical models, contribute to possible improvements and choose the best model(s) to be part of a new model for the prediction of the behaviour of confined columns under bending and compression. For circular columns, a wide group of authors have proposed several models specific for FRP-confined concrete. The analysis of some of the existing models was carried out by comparing these with several tested columns. Although several models predict fairly the peak load only few can properly estimate the load-strain and dilation behaviour of the columns. Square columns confined with CFRP show a more complex interpretation of their behaviour. Accordingly, the analysis of two experimental programs was carried out to propose new modelling equations for the whole behaviour of columns. The modelling results show that the analytical curves are in general agreement with the presented experimental curves for a wide range of dimensions. An analysis similar to the one done for circular columns was this turn carried out for square columns. Few models can fairly estimate the whole behaviour of the columns and with less accuracy at all levels when compared with circular columns. The second part of this study includes seven experimental tests carried out on reinforced concrete rectangular columns with rounded corners, different damage condition and with confinement and longitudinal strengthening systems. It was concluded that the use of CFRP confinement is viable and of effective performance enhancement alone and combined with other techniques, maintaining a good ductile behaviour for established threshold displacements. As regards the use of external longitudinal strengthening combined with CFRP confinement, this system is effective for the performance enhancement and viable in terms of execution. The load capacity was increased significantly, preserving also in this case a good ductile behaviour for threshold displacements. As to the numerical nonlinear modelling of the tested columns, the results show a variation of the peak load of 1% to 10% compared with tests results. The good results are partly due to the inclusion of the concrete constitutive model by Mander et al. modified by Faustino, Chastre & Paula taking into account the confinement effect. Despite the reasonable approximation to tests results, the modelling results showed higher unloading, which leads to an overestimate dissipated energy and residualdisplacement.